Análise de tarifação de energia elétrica: um estudo de caso na Ufersa Campus Caraúbas - Morais, Igno Florêncio de (Universidade Federal Rural do Semi-Árido, 2018)
In recent years a number of changes have been implemented in charging systems, this is directly reflected in the consumer's pocket, who realizes the difference when it comes to paying your electric bill, in the face of this problem, there is much talk about energy consumption efficiently, smart use and energy saving. Aiming to raise proposals that present ways to reduce the electricity bill values of the rural federal university of the semi-arid – UFERSA, Campus Caraúbas. An analysis was made of all invoices for the year 2017, in order to draw the energy profile of UFERSA. Looking at the invoices from January to December 2017, verified an excessive spending with the active consumption in the tip, from 5:30pm to 8h30pm, hours of intense activity on campus, which. It was noticed that the amount spent with the reactive consumption surplus outside the tip, corresponds to 9% of total invoices, which could be reduced with a feasibility study of the implementation of a capacitor bank. Another point analyzed was the comparison between contracted demand and measured demand, there was a significant difference, which is a study with COSERN, aiming at a reduction in the value contracted, presenting thus, a reduction in the invoice's final value.
Monografia
Keywords: Economia de energia; Consumidor; Tarifação; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA